Knowledge and Awareness about Leishmaniasis Disease in the General Public of Quetta, Pakistan - Ahmed, Tanzeel; Jadoon, Sarmad Sheraz; Waqas, Muhammad; Ammar, Muhammad; Jian, Liguo; Zhang, Qi (Journal of Pharmacy Practice and Community Medicine)
Aim: This study attempted to assess knowledge and awareness about Leishmaniasis disease in Quetta city, Pakistan. Materials and Methods: This was a questionnaire-based cross-sectional survey where 387 study respondents were targeted using the non-probability convenience sampling method for data collection. SPSS v 22.0 was applied for data analysis and P≤0.05 was considered statically significant. The Mann-Whitney and Kruskal-Wallis tests were performed to discover the relationship among variables. Results: Most respondents were from the age group 18-27 years 269 (69.5%) majority of whom were female 244 (64.0%). Most of the respondents had improved knowledge (73.6%), about the word Leishmaniasis, 50.6% of respondents were aware of the signs and symptoms, 54.8% of respondents were aware of the diagnosis, 64.3% of respondents had improved knowledge about treatment, 62.5% of the study population were aware of prevention and 40.8% of study respondents knew about the vaccination for leishmaniasis. Conclusion: This study exposed an overall better knowledge and awareness among the public about leishmaniasis disease and its causative agents, symptoms, diagnosis, treatment, prevention, and vaccination.
Keywords: Knowledge; Awareness; Leishmaniasis disease; Public; Quetta; Pakistan